Innovative Approaches to User Expectation Classification in E-commerce Mobile Apps Using Fuzzy Kano Model Approach - Karakurt, Necip; Corlu, Selcuk (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
This study aims to determine the design features that affect mobile application design and to classify these features according to customer perception. The methodology involved an exhaustive examination of Turkish mobile applications, consultations with an expert academic, scrutiny of forum pages, and an extensive literature review. Subsequently, the categorization of these features based on customer satisfaction was pursued through a survey conducted with 525 participants. The suggested fuzzy methods play a crucial role in mitigating information loss associated with crispness, presenting a promising avenue to enhance the accuracy of user expectation classification in e-commerce mobile applications. The findings of this study are expected to provide insights into how mobile application features differ across various demographic group. The Attractive features identified include One-Step Registration, Augmented Reality, Wishlist, Personalized Customer Experience, Fast Payment, Offline Features, Sale Progress Bar, Easy Browsing, Share Button, Loyalty Program, Product Comparison, Shipping Flexibility, and Barcode Scanning.
Keywords: User experience; Mobile Apps; Fuzzy Kano Model; WEBSITE DESIGN; PRODUCT CONFIGURATION; USABILITY; ATTRIBUTES; PREFERENCE; AESTHETICS; QUALITY; Computer Science; Mathematics